Development and Evaluation of a Real-World Outcomes-Based Tool to Support Informed Clinical Decision Making in the Palliative Treatment of Patients With Metastatic NSCLC. (2021) - Cramer-van der Welle, Christine M.; Kastelijn, Elisabeth A.; Plouvier, Bram C.; van Uden-Kraan, Cornelia F.; Schramel, Franz M. N. H.; Groen, Harry J. M.; van de Garde, Ewoudt M. W.
Abstract : PURPOSE: To develop and evaluate a tool for patients with stage IV non–small-cell lung cancer and their thoracic oncologists (TOs) that provides insight into real-world effectiveness of systemic treatments to support informed clinical decision making in the palliative setting. METHODS: A participatory design approach was used to acquire insights from patients and TOs into preferences regarding the content and design of the web-based tool. Implementation was investigated by means of an adoption and usage rate. The appreciation of the tool was evaluated through a telephone survey with patients and a questionnaire for TOs. RESULTS: From clinical data of 2, 989 patients with stage IV non–small-cell lung cancer diagnosed in one of the Santeon hospitals, an interface was developed to show treatments plus both real-world outcomes and clinical trial results after selecting patient characteristics (patients like me). This prototype of the tool was finalized after discussion in a focus group with four TOs and semi-structured interviews with six patients. The tool was implemented and used by TOs in three of six Santeon hospitals (50% adoption rate). The tool was used in 48 patients (29% usage rate), of which 17 participated in the telephone survey. Ten TOs responded to the questionnaire. The responses varied from positive reactions on the clear overview of treatment outcomes to statements that the tool rarely changed treatment decisions. Overall, the majority of patients and TOs scored the tool as of added value (71% and 83%, respectively). CONCLUSION: Our real-world data tool in metastatic lung cancer was appreciated in clinical practice by both patients and TOs. However, the efficacy of the implementation can be improved.